Analisis Literatur Tentang Penerapan Pendidikan Multikultural Di Tingkat Sekolah Menengah Pertama - Amaluddin Amaluddin; Ubabuddin Ubabuddin (Journal on Education, 2025)
This study examines the implementation of multicultural education in Indonesian Junior High Schools (SMP), aiming to explore and evaluate innovative strategies in creating a more inclusive and harmonious learning environment. Through a systematic literature review methodology, the research analyzes various academic references to understand best practices in implementing multicultural education. The findings reveal diverse approaches adopted by various junior high schools, including the integration of democratic and humanistic values in the curriculum and the development of extracurricular programs that support cross-cultural understanding. Key findings indicate that schools adopting a holistic approach, integrating both curricular and extracurricular aspects, demonstrate higher success rates in creating inclusive learning environments. This research contributes to the development of effective multicultural education models at the junior high school level, concluding that successful implementation depends on the systematic integration of diversity values, school community support, and student-centered learning methods. The research findings have significant implications for developing educational policies to address the needs of an increasingly diverse society.